Implementasi Disiplin Positif Melalui Kesepakatan Kelas dalam Meningkatkan Kedisiplinan Belajar Siswa Kelas IV - Faridatul Yuniar; Agung Setyawan; Sih Widayati; Zahrilia Nourhasanah (eductum: Jurnal Literasi Pendidikan, 2024)
Research is descriptive qualitative with data collection techniques in the form of interviews and documentation. The research results show that class agreement is significantly important in forming students' discipline in learning. Agreements made together between teachers and students encourage active participation by students so that they feel responsible for the rules that have been set. The application of positive discipline through class agreements has a positive impact on changes in student behavior, especially in terms of time discipline, responsibility, and mutual respect. However, there are challenges in applying it to students with hyperactive characteristics, which require a more flexible and consistent approach. Therefore, this research was conducted to implement positive discipline through class agreements in improving student discipline and creating a conducive learning atmosphere.